Prime Example Ingress Reframing the Pervasive Game Design Framework (PGDF) - Heinrich Söbke (International Journal of Serious Games, 2017)
The growing availability of mobile communication infrastructure over the last decade has contributed significantly to the maturity of Pervasive Gaming. The massive success of games such as Ingress and Pokémon Go made pervasive gaming a viable option for transforming learning. By its adaptability to location and context, pervasive technology is a valuable support for the design of engaging learning experiences. Despite profound examples of pervasive gaming as learning tool, there is still a lack of reliable methodologies to construct purposeful pervasive learning experiences. The Pervasive Game Design Framework (PGDF) is intended to fill this gap. In this article, we present the PGDF using the example of Ingress. Ingress is a prominent pervasive game, as it has received huge attention since its appearance in 2012. A large community of players and third-party-tool suppliers has created a rich set of experiences since then. In this research, we examine Ingress according to PGDF’s categories based on a survey among long-term Ingress players (N=133). Founded on this analysis we identify three main benefits for Ingress players. Furthermore, we discuss the consequences of these findings on the PGDF. Summarizing, this work strengthens the applicability of the PGDF, in order to enable the construction of enriched pervasive learning experiences.